PEMANFAATAN ECENG GONDOK UNTUK MEMBERSIHKAN KUALITAS AIR SUNGAI SUNGAI GADJAHWONG YOGYAKARTA - Setyanto, Kris; -, Warniningsih (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
River is one source of water is important sanga ang existence, in urban areas are often neglected maintenance stream. Many found the river full of garbage, not flowing and odorless. Gadjahwong River is one of the river in Jogjakarta through the city of Jogjakarta, there right dikiri industrial areas such as SGM milk factory, leather factory, etc. Budi Makmur. These rivers across the eastern part of the city of Jogjakarta, the secondary data and previous studies the parameters of BOD, COD, TSS and high Poop coli can be used as raw drinking water, can only be used for irrigation and agriculture. The method used in this study is first to determine the area of the river, installing nets to grow sisal plant, water hyacinth breeding. kmeudian test characteristics of river water before treatment. The next test stream water purification with water hyacinth after sam-pling continued with before, in the group after group of plants and water hyacinth plants, carried out per 2 weeks for 2 months. Based on the data for all parameters studied pollutants were water-quality parameters for turbidity, color, COD, BOD, Fe and ammonia from time to time is always changing levels. There is a tendency to decrease pollutant parameters hyacinth clumps position that more and more.